Retinal Neovascularization in Two Patients with Incontinentia Pigmenti - Dwiyana RF; Banjarnahor ID; Diana IA; Gondokaryono SP; Effendi RMRA; Feriza V (Dove Medical Press, 2022)
Reiva Farah Dwiyana, Ivan Daniel Banjarnahor, Inne Arline Diana, Srie Prihianti Gondokaryono, Raden Mohamad Rendy Ariezal Effendi, Vina Feriza Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran-Dr.Hasan Sadikin Hospital, Bandung, IndonesiaCorrespondence: Reiva Farah Dwiyana, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Bandung, Indonesia, Tel +62811247474, Email reiva@unpad.ac.idAbstract: Incontinentia pigmenti (IP) is a rare genodermatosis, inherited in an X-linked dominant pattern, making it generally found among women. Among several characteristics of IP are four phases of skin manifestation that tend to follow Blaschko's lines, in addition to abnormalities of the eye, central nervous system (CNS), and teeth. Ocular involvement in IP patients can occur since birth, which can be classified into retinal or non-retinal disorders. Retinal disorders can result in detachment, which is a major ocular threat for IP patients. This article reports two IP cases with overlapped phases of skin disorders in baby girls with ocular manifestations since early life. Clinical signs and additional examination of the skin and eyes are utilized to make the diagnosis. All the features of the histopathological examination supported the diagnosis of IP, and ocular exams revealed abnormalities in the form of retinal neovascularization (RN). Although RN may resolve spontaneously, patients should be monitored for the development of other eye disorders such as visual impairment.Keywords: genodermatosis, incontinentia pigmenti, ocular manifestation, retina